STUDENTS’ PERCEPTION ON THE USE OF GOOGLE CLASSROOM IN ENGLISH ONLINE LEARNING AT A RURAL JUNIOR HIGH SCHOOL - Periani, Ketut; P. E. D, Suputra (Universitas Pendidikan Ganesha, 2021)
The COVID-19 pandemic has caused the learning process initially done in class to turn into online learning. It causes teachers to need media to support online learning. The current problem is the limited student network due to geographical conditions. The students were also confused about operating Google Classroom under certain conditions due to a lack of knowledge about using the pedagogical platform. This study aimed to analyze students' perceptions of the use of google classroom in online English learning in rural high schools. This research was designed using a qualitative study. Data was collected through 2 instruments, namely questionnaires and interviews. Then, Miles and Huberman's theory is used in analyzing data where data analysis consists of four parts: data collection, data reduction, data presentation, and conclusion drawing/verification. The study results are. First, students' perceptions of Google Classroom as an online learning medium are categorized as positive. Second, the obstacles faced by students during the implementation of Google Classroom in online learning are limited interaction between students because students focus on interacting with teachers, and students consider Google Classroom ineffective because it cannot adapt to applications as seen from student responses when some of them do not understand about features in Google Classroom. Third, students have complaints when accessing Google Classroom where students cannot join classes because they do not have cellular data, which means they cannot access Google Classroom and cannot study online courses. Fourth, students are late submitting assignments because they are waiting for cellular and internet data. It can be concluded that the use of google classroom in learning experiences several obstacles, so it needs to be considered.